The Asian bush mosquito Aedes japonicus japonicus (Diptera: Culicidae) in Europe, 17 years after its first detection, with a focus on monitoring methods - Koban, Marcel B. (Parasit Vectors, 2019)
After the first detection of the Asian bush mosquito Aedes japonicus japonicus in the year 2000 in France, its invasive nature was revealed in 2008 in Switzerland and Germany. In the following years, accumulating reports have shown that Ae. j. japonicus succeeded in establishing in several European countries. Surveillance efforts suggest that there are currently four populations in Europe, with the largest one, formed by the recent fusion of several smaller populations, ranging from West Germany, with extensions to Luxembourg and French Alsace, southwards to Switzerland and continuing westwards through Liechtenstein to western Austria. This paper summarises the present distribution of Ae. j. japonicus in Europe, based on published literature and hitherto unpublished findings by the authors, and critically reviews the monitoring strategies applied. A proposal for a more standardised monitoring approach is provided, aiming at the harmonisation of future data collections for improving the comparability between studies and the suitability of collected data for further research purposes, e.g. predictive modelling approaches.